Transivity of President Joko Widodo's Speech in Preparation for the G20 Summit - Adi Sutrisno; Indra Tjahyadi (Journal on Education, 2024)
This study analyzed the participants, processes and circumstance as a medium for presenting ideas and experiences of speakers in President of Joko Widodo's speech and their relation to the context of the situation in the text. This research is qualitative research using Functional Systemic Linguistic theory. The main source of the data is President of Joko Widodo’s speech regarding the preparation plan for the 2022 G20 Summit activities accessed through the official website of the Cabinet Secretariat of the Republic of Indonesia. This study used the note-taking technique to record the speech before dividing it into clause pieces. The results of this research are found three elements namely participants, processes and circumstance. The participants are found human and non-human participants. Human participants are the most likely participants with an 87% of appearances. The processes are found material, mental, verbal and relational processes. The verbal process is the process that occurs the most with a percentage of occurrence as much as 60%. The circumstance are found in the speech namely; circumstantial cause, problem, range, location and role. Circumstance of location that refers to time occurs the most with a percentage of 38%. Based on the analysis of transitivity and related to the context of the situation, it can be seen that President Joko Widodo wants to inform the general public, both domestically and abroad, about the preparations that have been made by Joko Widodo as chairman of the 2022 G20 Summit activities and the issues to be discussed at the event.